Preparation method and application of Cu / Mn bimetallic doped cerium oxide catalytic material
By doping copper and manganese into the cerium oxide catalytic material and adding silk fibroin, Cu/Mn bimetal doped cerium oxide catalytic material with high catalytic activity and stability was prepared, which solved the problem of poor catalytic toluene oxidation performance in the prior art, and achieved a low-cost and efficient catalytic oxidation effect of toluene.
Patent Information
- Application Number
- CN202411481625.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art lacks stable, reliable and low-cost catalysts in catalytic oxidation of toluene. Precious metal catalysts have limited their industrial applications due to their high cost and poor thermal stability.
The preparation method of Cu/Mn bimetallic doped cerium oxide catalytic material is adopted. By adjusting the molar ratio of copper, manganese and cerium, and adding silk fibroin to the cerium oxide catalytic material, the catalytic material is obtained by hydrothermal treatment and high-temperature calcination.
The catalytic activity and stability of the catalytic material are improved, the ignition temperature of toluene conversion is reduced, and the catalytic oxidation performance of p-toluene is enhanced. At 450°C, the toluene conversion rate is first reached 90%.
Smart Images

Figure CN119909700A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of toluene catalytic materials, and in particular relates to a Cu / Mn bimetallic doped oxidizing agent. Preparation method and application of cerium catalytic material. Background Art
[0002] With the progress of industrialization, the problem of air pollution has become increasingly serious, and the emission of volatile organic compounds (VOCs) has attracted widespread attention. VOCs are mainly caused by transportation and industrial production processes, which not only lead to various air pollution problems, such as photochemical smog, but also seriously threaten human health. VOCs come from a wide range of sources, mainly from the petrochemical industry, pharmaceutical industry, decoration coatings industry and transportation activities, and are characterized by large emissions and strong secondary pollution. Toluene is the core representative pollutant of VOCs. Direct contact between the human body and toluene can cause health-related problems, such as respiratory irritation, liver and brain damage, damage to the reproductive system and nervous system, and even induce cancer. Therefore, it is necessary to develop effective technologies to reduce or even eliminate toluene emissions. It has become an important research field.
[0003] At present, the common treatment technologies for VOCs represented by toluene are mainly: adsorption, catalytic oxidation, biodegradation, membrane separation, etc. Among them, catalytic oxidation is considered to be a very promising technology because of its lack of secondary harmful pollutants, energy saving, environmental protection, and low operating cost. Catalysts are the core of catalytic oxidation technology. However, this technology still lacks stable and reliable catalysts in industrial applications. Therefore, it is of great significance to construct catalysts with excellent activity, good durability, and low cost and high efficiency for catalytic oxidation of toluene. At present, precious metal catalysts have been used for catalytic oxidation of VOCs due to their high activity at low temperatures. However, this type of catalyst has high cost, low global storage, and poor thermal stability, which limits its wide industrial application. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a preparation method and application of a Cu / Mn bimetallic doped cerium oxide catalytic material.
[0005] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a Cu / Mn bimetallic doped cerium oxide catalyst material, the method comprising the following steps: Step 1. Weigh the copper source, manganese source and cerium source in a molar ratio of (1-5): (1-5): 4 into a beaker and add deionized water to dissolve; Step 2, weigh 0.1-2g of silk fibroin and add it to the solution obtained in Step 1; Step 3, while stirring the solution obtained in Step 2, add a sodium hydroxide (NaOH) solution with a concentration of 1-5 mol / L, wherein the amount of the NaOH solution added is 1-5 mL, and continue stirring after the addition is completed, and the stirring time is 0.2-0.8 h; Step 4, transfer the solution obtained in Step 3 to a polytetrafluoroethylene liner, load it into a reaction kettle, and place it in an oven for hydrothermal aging, wherein the temperature of the hydrothermal aging is 10-120° C. and the time is 2-8 hours; Step 5, after the reaction is completed, take out the reactor and cool it, filter and wash the obtained solution, wash the precipitate with deionized water and ethanol respectively, and put the washed sample into an oven for drying; Step 6. The next day, the dried sample is placed in a muffle furnace and calcined at 100-700° C. for at least 4 hours, and then ground to obtain the Cu / Mn bimetallic doped cerium oxide catalytic material.
[0006] Furthermore, the molar ratios of the copper source, the manganese source and the cerium source are 1:5:4, 2:4:4, 3:3:4, 4:2:4 and 5:1:4.
[0007] Furthermore, the molar ratio of the copper source, the manganese source and the cerium source is 1:5:4.
[0008] Furthermore, the copper source, manganese source and cerium source are copper nitrate trihydrate, manganese nitrate and cerium nitrate hexahydrate respectively.
[0009] Furthermore, the precipitate is centrifugally washed with deionized water and ethanol respectively to remove impurities on the surface of the precipitate.
[0010] Furthermore, the calcination temperature is 550°C.
[0011] The method prepares the Cu / Mn bimetallic doped cerium oxide catalytic material.
[0012] The Cu / Mn bimetallic doped cerium oxide catalyst material prepared by the method is used in catalytic oxidation of toluene.
[0013] The present invention simultaneously dopes copper and manganese into the cerium oxide catalytic material. The synergistic advantage of the bimetallic doping helps to improve the lattice oxygen concentration and mobility, thereby improving the catalytic activity of the cerium oxide catalytic material; silk fibroin is a natural high-molecular fiber protein extracted from silk, and the addition of silk fibroin can effectively protect the cerium oxide crystals from being destroyed and inhibit the crystal growth during oxidation, thereby improving the catalyst stability. At the same time, the silk fibroin forms a complex with the cerium oxide, which can further improve the activity of the catalyst.
[0014] The co-introduction of copper and manganese enhances the catalytic oxidation performance of cerium oxide catalyst materials for toluene, improves the conversion efficiency of toluene, and reduces the ignition temperature of toluene conversion, but a large amount of copper will lead to a decrease in catalytic activity.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The Cu / Mn bimetallic doped cerium oxide catalytic material prepared by the method of the present invention has a large specific surface area and can absorb oxygen and Ce on the surface. 3+ The increase in content promotes the formation of more oxygen vacancies. The synergistic advantage of bimetallic doping helps to increase the lattice oxygen concentration and mobility, thereby improving the catalytic activity of cerium oxide catalytic materials, effectively reducing the ignition temperature of toluene conversion, and enhancing the catalytic oxidation performance of toluene. The toluene conversion rate of 90% is first reached at 450°C, and it can be used as a catalyst for the effective conversion of toluene. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The SEM and EDS images of the Cu / Mn bimetallic doped cerium oxide catalyst material prepared in Example 1; Figure 2 XRD patterns of Cu / Mn bimetallic doped cerium oxide catalyst materials prepared in Examples 1 to 5; Figures 3(a), 3(b), 3(c), 3(d), and 3(e) are full scan, O 1s orbital, Ce 3d orbital, Mn 2p orbital, and Cu 2p orbital XPS spectra of the Cu / Mn bimetallic doped cerium oxide catalytic materials prepared in Examples 1 to 5, respectively; FIG4 (a) and FIG4 (b) are N2 adsorption-desorption and pore size distribution curves of the Cu / Mn bimetallic doped cerium oxide catalytic materials prepared in Examples 1 to 5, respectively; Figure 5 This is a graph showing the catalytic oxidation performance of the Cu / Mn bimetallic doped cerium oxide catalytic material prepared in Examples 1 to 5 for toluene. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0018] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0019] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described in the present invention can also be used in the practice or testing of the present invention.
[0020] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to. Example 1
[0021] A preparation process of a Cu / Mn bimetallic doped cerium oxide catalytic material is as follows: Weigh 0.0008mol:0.004mol:0.0032mol of copper nitrate trihydrate, manganese nitrate and cerium nitrate hexahydrate (the molar ratio of copper, manganese and cerium is 1:5:4) and place them in a beaker, record them as 1Cu5Mn4Ce, dissolve them in 55mL of deionized water, weigh 1g of silk fibroin and add them to the beaker, add 5mL of NaOH solution with a concentration of 3 mol·L-1 to the solution under stirring, continue stirring for 0.5h, then transfer the solution to a polytetrafluoroethylene liner, put it into a reactor, and put it in an oven for hydrothermal aging at 120℃ for 6h; after the reaction is completed, take out the reactor and cool it, filter and wash the obtained solution, wash the precipitate with deionized water and ethanol for 3 times each, then put the sample obtained by filtration into an oven for drying; the next day, put the sample in the oven into a muffle furnace, heat it to 550℃ at a rate of 5℃·min-1, and keep the temperature constant for 4 h, remove the protein by high temperature calcination, and finally grind to obtain the required Cu / Mn bimetallic doped cerium oxide catalytic material.
[0022] The scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) images of the Cu / Mn bimetallic doped cerium oxide catalyst material prepared in this example are shown in FIG. Figure 1 As shown, it can be seen that under the induced synthesis of silk fibroin, the nanoparticles of Cu / Mn bimetallic doped cerium oxide catalytic materials present a certain spherical and sponge morphology, showing small agglomerates and uniform distribution. Small pores formed by the accumulation of oxide nanoparticles can be observed on the rough surface; the distribution of Mn, Ce and Cu elements of the copper-manganese-cerium composite material induced by silk fibroin was obtained by EDS analysis. Red, blue and green represent Mn, Ce and Cu elements, respectively. It can be clearly observed that the three elements are evenly distributed on the catalyst surface. Example 2
[0023] A preparation process of a Cu / Mn bimetallic doped cerium oxide catalytic material is as follows: Weigh 0.0016mol:0.0032mol:0.0032mol of copper nitrate trihydrate, manganese nitrate and cerium nitrate hexahydrate (the molar ratio of copper, manganese and cerium is 2:4:4) and put them in a beaker, record them as 2Cu4Mn4Ce, dissolve them in 55 mL of deionized water, weigh 1 g of silk fibroin and add it to the beaker, and add 3 mol·L -1 5 mL of NaOH solution was added and stirred for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into the reactor shell, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled. The obtained solution was filtered and washed. The precipitate was washed 3 times with deionized water and ethanol respectively. The sample obtained by filtration was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C min -1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired Cu / Mn bimetallic doped cerium oxide catalytic material was obtained by grinding. Example 3
[0024] A preparation process of a Cu / Mn bimetallic doped cerium oxide catalytic material is as follows: Weigh 0.0024mol:0.0024mol:0.0032mol of copper nitrate trihydrate, manganese nitrate and cerium nitrate hexahydrate (the molar ratio of copper, manganese and cerium is 3:3:4) and put them in a beaker, record them as 3Cu3Mn4Ce, dissolve them in 55mL of deionized water, weigh 1g of silk fibroin and add it to the beaker, and add 3mol·L -1 5 mL of NaOH solution was added and stirred for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into the reactor shell, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled. The obtained solution was filtered and washed. The precipitate was washed 3 times with deionized water and ethanol respectively. The sample obtained by filtration was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C·min -1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired Cu / Mn bimetallic doped cerium oxide catalytic material was obtained by grinding. Example 4
[0025] A preparation process of a Cu / Mn bimetallic doped cerium oxide catalytic material is as follows: Weigh 0.0032 mol:0.0016 mol:0.0032 mol of copper nitrate trihydrate, cerium nitrate hexahydrate, manganese nitrate and cerium nitrate hexahydrate (the molar ratio of copper, manganese and cerium is 4:2:4) and put them in a beaker, record them as 4Cu2Mn4Ce, dissolve them in 55 mL of deionized water, weigh 1 g of silk fibroin and add it to the beaker, and add 3 mol·L -1 5 mL of NaOH solution was added and stirred for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, placed in the reactor shell, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled. The resulting solution was filtered and washed. The precipitate was washed 3 times with deionized water and ethanol respectively. The sample obtained by filtration was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C min -1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired Cu / Mn bimetallic doped cerium oxide catalytic material was obtained by grinding. Example 5
[0026] A preparation process of a Cu / Mn bimetallic doped cerium oxide catalytic material is as follows: Weigh 0.004mol:0.0008mol:0.0032mol of copper nitrate trihydrate, manganese nitrate and cerium nitrate hexahydrate (the molar ratio of copper, manganese and cerium is 5:1:4) and put them in a beaker, record them as 5Cu1Mn4Ce, dissolve them in 55mL deionized water, weigh 1g of silk fibroin and add it to the beaker, and add 3mol·L -1 5 mL of NaOH solution was added and stirred for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into the reactor shell, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled. The obtained solution was filtered and washed. The precipitate was washed 3 times with deionized water and ethanol respectively. The sample obtained by filtration was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C·min -1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired Cu / Mn bimetallic doped cerium oxide catalytic material was obtained by grinding.
[0027] The Cu / Mn bimetallic doped cerium oxide catalytic material prepared above was characterized by X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and specific surface area analysis (BET). The characterization results are as follows: Figure 2This is the XRD spectrum of the Cu / Mn bimetallic doped cerium oxide catalytic material prepared in Examples 1-5. It can be seen from the figure that no characteristic peaks belonging to manganese oxide appear, indicating that Mn enters the cerium oxide lattice to form a solid solution; the 2θ values of the main X-ray diffraction peaks of the Cu / Mn bimetallic doped cerium oxide catalytic material are all at about 28.55°, 33.08°, 47.48°, and 56.33°, which are all characteristic diffraction peaks of cerium oxide and are respectively attributed to the (111), (200), (220), and (311) crystal planes of the face-centered cubic fluorite structure (JCPDS34-0394); in addition to the characteristic peaks belonging to cerium oxide, for the Cu / Mn bimetallic doped cerium oxide catalytic material prepared in Example 2-5, characteristic peaks of copper oxide (JCPDS45-0937) belonging to the monoclinic phase structure also appear at 2θ values of about 35.54° and 38.73°, and the peak intensity increases with the increase of Cu content, indicating that with the increase of Cu content, the amount of copper entering the cerium oxide lattice reaches saturation, and copper oxide crystals are formed at this time.
[0028] Figures 3 (a) to 3 (e) are full scans, O1s orbitals, Ce 3d orbitals, Mn 2p orbitals, and Cu 2p orbital XPS spectra of the Cu / Mn bimetallic doped cerium oxide catalytic materials prepared in Examples 1 to 5, revealing their elemental composition and chemical state. From the full scan spectra shown in Figure 3 (a), it can be seen that the prepared Cu / Mn bimetallic doped cerium oxide catalytic materials all contain C, O, Ce, Mn, and Cu elements.
[0029] From the O 1s orbital spectrum shown in Figure 3 (b), it can be seen that the fitted O 1s spectrum shows three characteristic peaks of different oxygen forms. The characteristic peaks at 529.35 eV~529.68 eV correspond to lattice oxygen (O latt ) peaks, and the characteristic peaks at 531.33 eV~531.69 eV correspond to the surface adsorbed oxygen (O ads ) peaks, and the characteristic peaks at 532.88 eV~533.54 eV correspond to the surface hydroxyl oxygen (O OH The surface adsorbed oxygen content α (O ads ), the order from large to small is 4Cu2Mn4Ce, 1Cu5Mn4Ce, 3Cu3Mn4Ce, 2Cu4Mn4Ce, 5Cu1Mn4Ce. The prepared Cu / Mn bimetallic doped cerium oxide catalytic materials all have higher surface adsorbed oxygen content, among which 4Cu2Mn4Ce catalytic material has the largest surface adsorbed oxygen content.
[0030] Figure 3 (c) is the XPS spectrum of the Cu / Mn bimetallic doped cerium oxide catalyst Ce 3d, with u used to mark the characteristic peak belonging to the Ce3d3 / 2 spin orbit, and v used to mark the characteristic peak belonging to the Ce 3d5 / 2 spin orbit. Among them, u′ (~885.79 eV) and v′ (~904.29 eV) belong to Ce 3+ The characteristic peaks of , while u (~901.11 eV), v (~882.66 eV), u′′ (~907.82 eV), v′′ (~889.07 eV), u′′′ (~916.84 eV) and v′′′ (~898.38 eV) are attributed to Ce 4+ characteristic peaks.
[0031] Figure 3 (d) is the XPS spectrum of Mn 2p of Cu / Mn bimetallic doped cerium oxide catalyst material. The characteristic peaks between 641.38 eV and 644.03 eV are attributed to Mn 2p3 / 2 spin orbits, and the characteristic peaks between 652.28 eV and 655.28 eV are attributed to Mn 2p1 / 2 spin orbits. Further fitting analysis of the characteristic peaks of Mn 2p3 / 2 spin orbits of 5Cu1Mn4Ce and 4Cu2Mn4Ce catalysts revealed that the peaks at lower binding energies (641.38 eV to 641.47 eV) are attributed to the Mn 2p1 / 2 spin orbit. 3+ The characteristic peaks of Mn at higher binding energy (643.98 eV~644.03 eV) are attributed to Mn 4+ characteristic peaks.
[0032] Figure 3 (e) is the XPS spectrum of Cu 2p of Cu / Mn bimetallic doped cerium oxide catalyst material. The characteristic peaks between 932.95 eV and 936.93 eV are attributed to the Cu 2p3 / 2 spin orbit, and the characteristic peaks between 952.56 eV and 956.41 eV are attributed to the Cu 2p1 / 2 spin orbit. In the Cu 2p spectrum, it can be clearly seen that the Cu 2+ The shake-up peak of the Cu 2p3 / 2 spin-orbit characteristic peak of the prepared Cu / Mn bimetallic doped cerium oxide catalyst was further fitted and analyzed. The peak at lower binding energy (932.95 eV~934.04 eV) was attributed to Cu (Cu-O) bound to lattice oxygen, and the peak at higher binding energy (934.79 eV~936.93 eV) was attributed to copper hydroxide.
[0033] Figures 4 (a) and 4 (b) are the N2 adsorption-desorption and pore size distribution curves of the Cu / Mn bimetallic doped cerium oxide catalyst materials prepared in Examples 1 to 5; as shown in Figure 4 (a), according to the IUPAC isotherm classification, all curves belong to the IV type isotherm with an H3 type hysteresis loop, which has the typical characteristics of microporous or mesoporous materials. From the pore size distribution curve shown in Figure 4 (b), it can be seen that all catalysts contain a large number of mesopores, and the pore size distribution is mainly distributed between 2 and 10 nm.
[0034] Table 1 lists the specific surface areas (S BET ), pore volume (V pore ) and average pore size. It can be seen from Table 1 that the 1Cu5Mn4Ce catalytic material prepared in Example 1 has the largest specific surface area and pore volume. With the increase of the doped copper content, the specific surface area of the prepared Cu / Mn bimetallic doped cerium oxide catalytic material decreases and the pore volume decreases.
[0035]
[0036] Table 1 The Cu / Mn bimetallic doped cerium oxide catalyst material prepared in Examples 1 to 5 was used to carry out a catalytic test on toluene, and the test process is as follows: A fixed bed reactor made of quartz was used. 100 g of the catalytic material prepared above was weighed and placed in a quartz reaction tube. Both ends were fixed with quartz wool. The quartz reaction tube was placed in a reactor and heated at 100 mL min. -1 High-purity air was introduced at a rate of 10°C·min -1 The temperature of the reactor was raised to 300°C at a speed of 100 °C, maintained for 30 min, and then naturally cooled to 50°C; the toluene solution was placed in a 15°C water bath, and high-purity air was bubbled into the quartz tube through the toluene solution. After maintaining at 50°C for 2 h, 75 μL of tail gas was collected and analyzed by gas chromatograph; after the toluene concentration in the tail gas was stable, the tail gas was heated at 2°C·min -1 The reactor temperature was raised to 450°C at a rate of , and the test exhaust gas was collected every 10 minutes.
[0037] The toluene conversion rate is calculated by the peak area of toluene in the low temperature zone and the high temperature zone. The specific calculation formula is as follows:
[0038] in, is the peak area of toluene in the tail gas before the toluene ignition temperature, It is the peak area of toluene in the exhaust gas at the test temperature after the toluene ignition temperature.
[0039] Figure 5The catalytic oxidation performance diagrams of toluene by the Cu / Mn bimetallic doped cerium oxide catalytic materials prepared in Examples 1 to 5 are shown, and Table 2 shows the corresponding ignition temperature and final toluene conversion rate of the catalytic oxidation of toluene.
[0040]
[0041] Table 2 from Figure 5 As can be seen from Table 2, the Cu / Mn bimetallic doped cerium oxide catalytic materials prepared in Examples 1 to 5 all exhibited excellent catalytic performance for toluene, and the 1Cu5Mn4Ce catalytic material prepared in Example 1 had the lowest ignition temperature of 250°C. Within the temperature range investigated, except for the 5Cu1Mn4Ce catalytic material prepared in Example 5, the catalytic materials prepared in Examples 1 to 4 all ultimately achieved a toluene conversion rate of 90%, and the order of toluene catalytic performance from high to low was: 1Cu5Mn4Ce, 3Cu3Mn4Ce, 4Cu2Mn4Ce, 2Cu4Mn4Ce, and 5Cu1Mn4Ce.
[0042] The results of catalytic oxidation of toluene show that the prepared Cu / Mn bimetallic doped cerium oxide catalytic material is beneficial to enhancing the catalytic oxidation performance of cerium oxide-based catalysts for toluene, but the catalytic activity decreases with the increase of Cu content.
[0043] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a Cu / Mn bimetallic doped cerium oxide catalyst material, characterized in that: The method comprises the following steps: Step 1. Weigh the copper source, manganese source and cerium source in a molar ratio of (1-5): (1-5): 4 into a beaker and add deionized water to dissolve; Step 2, weigh 0.1-2g of silk fibroin and add it to the solution obtained in Step 1; Step 3, while stirring the solution obtained in Step 2, add a sodium hydroxide (NaOH) solution with a concentration of 1-5 mol / L, wherein the amount of the NaOH solution added is 1-5 mL, and continue stirring after the addition is completed, and the stirring time is 0.2-0.8 h; Step 4, transfer the solution obtained in Step 3 to a polytetrafluoroethylene liner, load it into a reaction kettle, and place it in an oven for hydrothermal aging, wherein the temperature of the hydrothermal aging is 10-120° C. and the time is 2-8 hours; Step 5, after the reaction is completed, take out the reactor and cool it, filter and wash the obtained solution, wash the precipitate with deionized water and ethanol respectively, and put the washed sample into an oven for drying; Step 6. The next day, the dried sample is placed in a muffle furnace and calcined at a calcination temperature of 100-700° C. for at least 4 hours, and then ground to obtain the Cu / Mn bimetallic doped cerium oxide catalytic material.
2. The method for preparing a Cu / Mn bimetallic doped cerium oxide catalyst material according to claim 1, characterized in that: The molar ratios of the copper source, the manganese source and the cerium source are 1:5:4, 2:4:4, 3:3:4, 4:2:4 and 5:1:
4.
3. The method for preparing a Cu / Mn bimetallic doped cerium oxide catalyst material according to claim 1, characterized in that: The copper source, manganese source and cerium source are copper nitrate trihydrate, manganese nitrate and cerium nitrate hexahydrate respectively.
4. The method for preparing a Cu / Mn bimetallic doped cerium oxide catalyst material according to claim 1, characterized in that: In Step 5, the precipitate is centrifuged and washed with deionized water and ethanol respectively.
5. The method for preparing a Cu / Mn bimetallic doped cerium oxide catalyst material according to claim 1, characterized in that: The calcination temperature is 550°C.
6. The Cu / Mn bimetallic doped cerium oxide catalytic material prepared by the method for preparing a Cu / Mn bimetallic doped cerium oxide catalytic material according to any one of claims 1 to 5.
7. Use of the Cu / Mn bimetallic doped cerium oxide catalyst material according to claim 6 in catalytic oxidation of toluene.